Entre muros, celas e sombras: história oral de mulheres trabalhadoras de uma instituição prisional - Soares , Camila Carla Dantas (2017)
It is a qualitative research that used the technique of Oral Thematic History. The present study had as main objective: to know the history of penitentiary security agents of a female prison institution. The research was conducted at the Maria Júlia Maranhão Reeducation Center, located in the city of João Pessoa. The empirical material was produced from the interview with ten collaborators, the results of this material were discussed based on the vital tones of the narratives, which subsidized the construction of three thematic axes, as follows respectively: Motivations: Financial benefits, job stability and flexibility In the work scale; Penitentiary security agent: a mixture of feelings added to prejudice and lack of recognition; The price of being a penitentiary security agent: repercussions on the life and health of these women. These axes stimulated the discussion based on the comparison between the findings obtained through the interviews and the pertinent literature. This research respected the ethical and legal aspects that regulate Resolution 466/12 of the National Health Council, as well as of Resolution 311/2007 that deals with the ethics of nurses in scientific research. Being approved on 07/21/2016, under the CAAE: 56468016.7.0000.5188. The stories of the women workers revealed that the main motivations that led these women to the profession of penitentiary security were: financial benefits, job stability and flexibility in the work scale. They also revealed that they experience a mixture of feelings, among them fear, conflict of values, dissatisfaction and revolt related to prejudice and lack of recognition. It was also possible to perceive how this work activity can bring moments of "pleasure", but mainly of pain and suffering. For employees, although it is a profession of risk that affects the health of professionals, it also offers opportunities for learning and reflection on how to value more life and their families.